Pengaruh Dimensi Fraud Diamond Terhadap Perilaku Kecurangan Akademik (Studi Kasus Pada Mahasiswa Akuntansi Sektor Publik Politeknik Negeri Jember) - Mohammad Luthfil Amin; Abdun Dhorivun; Ayu Dewi Sintawati; Arisona Ahmad; Oryza Ardhiarisca (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
This research aims to discuss the influence of the fraud diamond concept, which consists of pressure, opportunity, rationalization, and capability on students' academic fraud behavior. This research is a type of quantitative research. The population in this study were D4 students of the Public Sector Accounting Study Program, Department of Agribusiness Management, Jember State Polytechnic class of 2018-2020. This study uses purposive sampling on taking the sample with the criteria that students are active in the Public Sector Accounting D4 Study Program and have committed or encountered academic fraud during college until a selection of 139 respondents was obtained. The results of this study indicate that pressure and opportunity have no significant effect on academic fraud behavior. In contrast, rationalization and capability substantially impact student academic fraud behavior.